Pengaruh Tepung Kulit Buah Naga Merah (Hylocereus polyrhizus) terhadap Potongan Komersial Karkas Ayam Broiler - Iis Yuanita; Efraim Tobias; Lisnawaty Silitonga (LPPM Universitas Palangka Raya, 2022)
This research was conducted to determine the effect of red dragon fruit peel meal on the weight and percentage of carcass, lower thigh, upper thigh, wing, breast, and back of broiler carcass. This research used a Completely Randomized Design (CRD) with 4 treatments and each treatment had 6 replications. The treatments were T0 = basal diet (BD) without dragon fruit peel meal (DPM), T1 = BD+0.5% DPM, T2 = BD+1% DPM and T3 = BD+1.5% DPM. The parameter were final weight, carcass weight and percentage, commercial cuts of carcass weight and percentage. The results of this study showed that the red dragon fruit (Hylocereus polyrhizus) peel meal in broiler chicken diet had no significantly effect on the final weight, carcass weight and percentage, and commercial cuts of carcass weight and percentage of broiler chicken. The diet with red dragon fruit peel meal up to 1.5% have no negative effect to broiler chickens.